Demonstration of a Genetic Factor Influencing Spontaneous Release of a Xenotropic Virus of Mouse Cells - Stephenson, John R. (1974)
There is increasing evidence that mouse cells of different strains contain different numbers and biologic classes of naturally-integrated type-C RNA viruses. The present studies have examined the cellular regulation of one class of virus, xenotropic in host range, which is common to mice of NIH Swiss and NZB strains. This virus is spontaneously released at high level by NZB embryo cells but its production by NIH Swiss embryo cells is below detectable levels. Quantitative analysis of the chronic level of virus release by embryo cell lines established in tissue culture from genetic crosses of NIH and NZB strains has demonstrated the existence of a partially dominant gene influencing virus release. Evidence is presented indicating that this gene may act to provide a factor necessary for expression of a specific class of endogenous virus.